2020
DOI: 10.3892/mmr.2020.10941
|View full text |Cite
|
Sign up to set email alerts
|

Oral intake of α‑glucosyl‑hesperidin ameliorates selenite‑induced cataract formation

Abstract: Hesperetin is a natural flavonoid with robust antioxidant properties. Our previous study reported that hesperetin can prevent cataract formation. However, an important consideration regarding hesperetin consumption is the limited bioavailability due to its poor solubility. The present study investigated the anti-cataract effects of α-glucosyl hesperidin in vivo and in vitro using a selenite-induced cataract model. SD rats (age, 13 days) were orally administered PBS (0.2 ml) or α-glucosyl hesperidin (200 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…A hesperidin derivate, alpha-glucosyl hesperidin, previously found in the orange peel by several authors [ 62 , 63 , 64 , 65 , 66 ] has been identified at time 8.481 min (peak 25). In addition, a naringin derivate found at peak 34 was assigned to naringin hydrate according with Iglesias-Carres et al [ 55 ] and Fayek et al [ 59 ].…”
Section: Resultsmentioning
confidence: 85%
“…A hesperidin derivate, alpha-glucosyl hesperidin, previously found in the orange peel by several authors [ 62 , 63 , 64 , 65 , 66 ] has been identified at time 8.481 min (peak 25). In addition, a naringin derivate found at peak 34 was assigned to naringin hydrate according with Iglesias-Carres et al [ 55 ] and Fayek et al [ 59 ].…”
Section: Resultsmentioning
confidence: 85%
“…Besides surgical removal of the cataractous lens and insertion of an artificial lens, there is no effective drug treatment to cure cataracts. It was reported that lens sclerosis and presbyopia are early observed symptoms of age-related nuclear cataract [ 2 ], and we previously reported that oral consumption of G-Hsd delayed the onset of cataract induced by sodium selenite [ 5 ]. So, we hypothesized that G-Hed could prevent lens sclerosis, and here we show that lens elasticity was maintained by G-Hsd treatment under the same experimental conditions ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, daily intake of antioxidants is a useful approach for the prevention of both presbyopia and cataract formation. In this study, we investigated the effects of hesperetin (Hst), a natural antioxidant, which we have previously reported to have anti-cataract effects in a selenite-induced cataract rat model [ 4 , 5 ]. Hst is the aglycone of hesperidin (Hsd), which is the major flavonoid in citrus fruits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that α-glucosyl-hesperidin (G-Hsd) prevents nuclear cataract formation induced by selenite administration [ 4 ]. G-Hsd was synthesized by the glycosylation process with hesperidin (Hsd), which is the major and abundant flavonoid found in citrus fruits.…”
Section: Introductionmentioning
confidence: 99%